Robust Contract Evolution in a TypeSafe MicroService Architectures - Seco, João Costa (2020)
This work was partially supported by FCT/MCTES grant PTDC/EEICTP/4293/2014. Publisher Copyright: © João Costa Seco, Paulo Ferreira, Hugo Lourenço, Carla Ferreira, and Lúcio Ferrão.